2022
DOI: 10.1186/s13065-022-00830-0
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling and equilibrium studies on the recovery of praseodymium (III), dysprosium (III) and yttrium (III) using acidic cation exchange resin

Abstract: In this research, the possibility of using hydrogenated Dowex 50WX8 resin for the recovery and separation of Pr(III), Dy(III) and Y(III) from aqueous nitrate solutions were carried out. Dowex 50WX8 adsorbent was characterized before and after sorption of metal ions using Fourier-transform infrared spectroscopy (FT-IR), Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Analysis (EDX) techniques. Sorption parameters were studied which included contact time, initial metal ion concentration, nitric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…The lower values of R 2 obtained for the Langmuir model showed that it did not fit well to the adsorption data. The maximum theoretical predicted adsorption of Pr(III) onto A. platensis constituted 99.3 mg/g, and this is higher than the values reported for other sorbents: 57.8 mg/g for crab shell and 49.9 mg/g for orange peel [45] and 30.0 mg/g for Dowex 50WX8 resin [49]. The capacity was comparable with the values obtained for Laminaria digitate (110-120 mg/g) [50] and lower than the values obtained for D72 resin (294 mg/g) [40].…”
Section: Praseodium Removal By Non-living a Platensis Biomass Under D...contrasting
confidence: 57%
“…The lower values of R 2 obtained for the Langmuir model showed that it did not fit well to the adsorption data. The maximum theoretical predicted adsorption of Pr(III) onto A. platensis constituted 99.3 mg/g, and this is higher than the values reported for other sorbents: 57.8 mg/g for crab shell and 49.9 mg/g for orange peel [45] and 30.0 mg/g for Dowex 50WX8 resin [49]. The capacity was comparable with the values obtained for Laminaria digitate (110-120 mg/g) [50] and lower than the values obtained for D72 resin (294 mg/g) [40].…”
Section: Praseodium Removal By Non-living a Platensis Biomass Under D...contrasting
confidence: 57%
“…Following publication of the original article [1], the author noticed the errors in Table 4 and in the reference list. These have been corrected with this erratum.…”
Section: Reference Listmentioning
confidence: 99%
“…So far the adsorption of many metals such as Cu(II), Fe(II), Pb(II), Cd(II), Zn(II), Bi(III), and Co(II) has been successfully performed using SIRs by the selection of suitable extractant 27 . The possibility of using hydrogenated Dowex 50WX8 resin for the recovery and separation of Pr(III), Dy(III) and Y(III) from aqueous nitrate solutions were carried out by Masry and coworkers and promising results were obtained in determined optimal operating conditions 28 .…”
Section: Introductionmentioning
confidence: 99%